A novel fibrinogen Bβ chain frameshift mutation in a patient with severe congenital hypofibrinogenaemia - Xu, Xiucai; Wu, Jingsheng; Zhai, Zhimin; Zhou, Rongfu; Wang, Xuefeng; Wang, Hongli; Ding, Kaiyang; Sun, Zimin; Ni, Heyu (Thrombosis and Haemostasis, 2006)
Congenital afibrinogenemia and severe hypofibrinogenemia are severe bleeding disorders characterized by either undetectable or very low levels of fibrinogen in patients’ plasma and platelets. A majority of the reported cases are caused by mutations in the fibrinogen Aα chain. In this study, we identified a genetic defect in the fibrinogen Bβ-chain (FGB) underlying severe hypofibrinogenemia. The propositus frequently displayed bleeding episodes with a prolonged blood-clotting time (thrombin time > 180 s,activated partial thromboplastin time > 300 s, prothrombin time > 120 s) and had a very low level of plasma fibrinogen (1.7–1.8 mg/dl). His parents had a consanguineous marriage, and their functional and immunological fibrinogen was approximately half of the normal level.The platelet fibrinogen level of the propositus could not be detected by western blotting, and his platelet aggregation was severely impaired. DNA screening of the whole fibrinogen gene revealed a homozygous GGGG→GGG mutation at nucleotide 7969–7972 in his FGB gene. The propositus’ parents are both heterozygous for this mutation. This mutation contributes to Gly419→Val, and the 419–434 codons are frame shifted, and a stop codon is formed at codon 435.The predicted truncated Bβ-chain is 27 amino acids shorter than the normal Bβ-chain and a central β-strand in the globular βC domain is absent,which may lead to destabilization of the entire β-domain. To the best of our knowledge, this is the first report of such a mutation which is associated with severe hypofibrinogenemia.
Keywords: Congenital hypofibrinogenemia / afibrinogenemia; fibrinogen / fibrin; gene mutation; platelet aggregation